Enrichment characteristics and dietary evaluation of selenium in navel orange fruit from the largest navel orange-producing area in China (southern Jiangxi) - Yao, Fengxian; Wen, Li; Chen, Rong; Du, Chao; Su, Shiming; Yan, Mengmeng; Yang, Zhonglan (Frontiers in Plant Science, 2022)
Diet is the main intake source of selenium (Se) in the body. Southern Jiangxi is the largest navel orange-producing area in China, and 25.98% of its arable land is Se-rich. However, studies on the Se-rich characteristics and Se dietary evaluation of navel orange fruits in the natural environment of southern Jiangxi have not been reported. This study was large-scale and in situ samplings (n = 492) of navel oranges in southern Jiangxi with the goal of investigating the coupling relationships among Se, nutritional elements, and quality indicators in fruits and systematically evaluating Se dietary nutrition to the body. The results indicated that the average content of total Se in the flesh was 4.92 µg∙kg-1, and the percentage of Se-rich navel oranges (total Se ≥ 10 µg∙kg-1 in the flesh) was 7.93%, of which 66.74% of the total Se was distributed in the pericarp and 33.26% in the flesh. The average content of total Se in the flesh of Yudu County was the highest at 5.71 µg∙kg-1. There was a significant negative correlation (p < 0.05) between Se, Cu, and Zn in the Se-rich flesh. Provide more Se dietary nutrition to the human body through Se-enriched navel oranges. The highest values of Se nutrient reference value (NRVse) and recommended Se nutrient intake (RNIse) are 7.97% and 15.95%, respectively. These findings will help to identify Se enrichment in navel orange fruit in China's largest navel orange-producing area and guide the selection of Se-rich soils for navel orange production in the future.